2016
DOI: 10.1111/myc.12555
|View full text |Cite
|
Sign up to set email alerts
|

Onychomycosis secondary to onychomadesis: an underdiagnosed manifestation

Abstract: Onychomycosis is a rare nail disorder in early childhood, while onychomadesis is a periodic idiopathic, non-inflammatory disease that affects the nail matrix and is common in children especially in those who suffer from viral infections. In this study, we investigated recent cases of onychomycosis subsequent to periods of onychomadesis in children. Sixteen young children (six males, 10 females) with a mean age of 36.5 months were diagnosed with onychomadesis, and 13 of the patients had a history of viral infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…46 Nail plate separation could increase the susceptibility of onychomycosis in onychomadesis-infected children. 48 In a case study of 16 children diagnosed with onychomadesis, 69% were found to be culture positive with Candida species revealed during microscopic examination. 48 As previously stated, the number of onychomycosis-diagnosed children over time has increased, with onychomycosis possibly becoming more prevalent in children.…”
Section: Childrenmentioning
confidence: 99%
“…46 Nail plate separation could increase the susceptibility of onychomycosis in onychomadesis-infected children. 48 In a case study of 16 children diagnosed with onychomadesis, 69% were found to be culture positive with Candida species revealed during microscopic examination. 48 As previously stated, the number of onychomycosis-diagnosed children over time has increased, with onychomycosis possibly becoming more prevalent in children.…”
Section: Childrenmentioning
confidence: 99%
“…Onychomadesis can be a predisposing factor for chloronychia or onychomycosis. An earlier report of Candida onychomycosis developing in a patient with onychomadesis following hand, foot, and mouth disease shows onychomadesis as a risk factor [17]. Lack of protection in our patient led to the initial damage to the nail unit with subclinical onychomadesis.…”
Section: Discussionmentioning
confidence: 71%
“…Conditions that cause nail matrix arrest include infections such as hand-foot-and-mouth disease and varicella, trauma, chemotherapy, anticonvulsants, lichen planus, and Kawasaki disease (32). Nails affected by onychomadesis are at risk of developing onychomycosis (33).…”
Section: Onychomadesismentioning
confidence: 99%